KAJIAN FILOSOFIS UPACARA MEACI ACI DI DESA ADAT BANYUNING KECAMATAN BULELENG KABUPATEN BULELENG (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2025)
Hindu religious ceremonies are customs that are considered to have been inherited andcontinue to be carried out by the community because they believe that the existing methods arethe best to be imitated and applied further. The meaci aci ceremony, which comes from areligious tradition, will be passed on to the next generation because it is part of the piodalanceremony at the Banyuning Village Temple. Based on this, the researcher formulated thefollowing problems, namely What is the Basic Basis for the Meaci Aci Ceremony in BanyuningTraditional Village, Buleleng District, Buleleng Regency?, What is the Form of the Meaci AciCeremony in Banyuning Traditional Village, Buleleng District, Buleleng Regency?. What isthe Philosophical Meaning of the Meaci Aci Ceremony in Banyuning Traditional Village,Buleleng District, Buleleng Regency?. This study uses a research method to ensure that thisresearch problem is correct, the author uses a qualitative research approach with a descriptiveapproach. Qualitative research aims to understand the natural phenomena experienced by theresearch subjects as a whole and by using various natural methods. In this study, the subjectsand objects of research are described in a natural context. This study uses the PurposiveSampling technique. In addition, data collection can be done through interviews, observations,literature, documentation, and data analysis. The results of this study are the BasicFoundations of the Meaci Aci Ceremony including: Religious Foundations, Socio-CulturalFoundations, Mythological Foundations. The form of the Meaci Aci Ceremony is carried outto close negative energy in the process of picking up tirta from the Batur temple to theBanyuning traditional village temple by going through the Nunas Tirta Ceremony, Mendak,Meaci Aci, Performing Prayers, Tata Linggih Ceremony, Distribution of Tirta. ThePhilosophical Meaning of the Meaci Aci Ceremony includes: Religious Meaning, RitualMeaning, Meaning of Togetherness, Meaning of Expression of Gratitude
Keywords: meaci aci ceremony, philosophical study